THE ROLE AND IMPORTANCE OF INVESTMENT POLICY IN ENSURING COMPETITIVENESS IN INTERNATIONAL MARKETS - Khudoyarov Anvar Aidjanovich (Journals Park Publishing, 2025)
According to international economic experience, the level of development of a country, that is, the development and economic growth of the economy, largely depends on the investment processes in the country. This is especially evident today, when the further development of any country depends on the effective and targeted attraction of investments.